Creating a GUI solver for linear programming models in MATLAB - Siaw, Chong Lee; Jia, Xin Chin (UTHM Publisher, 2018)
The concept of linear programming (LP) was developed to find out the best solution among all feasible solutions in an optimization problem. This technique becomes much popular and attains great attention from researchers due to its wide application in engineering, computer science, marketing, military and industries. Nowadays, there are many commercial software that apply this technique to solve optimization problems, e.g. Excel Solver, TORA, AMPL, LINGO and MATLAB. In this paper, we aim to use MATLAB to develop a Graphical User Interface (GUI) solver for LPs, namely LpSolver. The LP methods that will be included in our solver are the simplex method, the Big-M method, the Two-Phase method and the DualSimplex method. We try to make our solver perform calculations in symbolic form so that the result will be free from rounding errors. Besides that, we added a few features such as creating animated 2-D graphs and generating a detailed tableau showing all intermediate iterative results; in which the user can use it to trace the convergence path that leads to the optimal solution. In the later part of this paper we test our solver with a simple classroom sized problem.